Evaluation of Performance Trend of Candidates Disapproved in the Examination of Certification, Using Hierarchic Models - Lilia Carolina Carneiro da Costa; Nilo Batista da Silva Junior; Paulo Roberto Pinheiro Leal (Universidad Autónoma de Madrid, 2018)
The Occupational Certification for principals asses' if the candidate has the basic skills in order to practice the function of a school manager. This study aims at evaluating the tendency of the failed candidates' performance, i.e., to verify if they had presented better or worse results or if they keep the same level of knowledge/skills from one version to another one of the test. The relation of the tendency of the candidates' performance in the tests with the demographic characteristics of the same ones, such as sex and age, was also studied by means of multivariate hierarchical models. This study shows that, as a rule, failed candidates improve their performances in the subsequent versions of the tests. Moreover, the profile of the candidate with a bigger trend in acquiring more knowledge/skills between the versions is that of the younger teacher.